UIN Maulana Malik Ibrahim Malang's Strategic Policy in Encouraging Local Economic Collaboration - Fitria Amalia Dewi (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper analyzes the policy issues related to the weak collaboration between UIN Maulana Malik Ibrahim Malang and local economic stakeholders, which has resulted in limited community economic empowerment. Using qualitative methods and a comprehensive policy analysis approach, this policy paper identifies the root cause: the absence of a formal mechanism regulated by the university's internal regulations to integrate input from MSMEs, industry, and local government. This gap results in curriculum irrelevance to job market needs, underutilization of academic innovation, and a lack of practical skills for graduates. Using USG (Urgency, Seriousness, Growth) analysis and policy alternative criteria scoring theory, this article highlights the urgency of this issue and the need for systemic intervention. The results suggest that the most effective policy alternative is the establishment of a permanent multi-actor curriculum partnership forum, as stipulated in the Rector's Regulation. This forum will serve as a formal bridge to ensure the curriculum and innovation programs remain relevant to local economic dynamics. These policy recommendations are expected to strengthen the synergy between UIN Malang and the surrounding economic ecosystem, thereby increasing the university's tangible contribution to sustainable regional development.